Boosting C-C Coupling for Electrochemical CO2 Reduction over Novel Cu-Cubic Catalysts with an Amorphous Shell - Hanlin Wang; Tian Wang; Gaigai Dong; Linbo Zhang; Fan Pan; Yunqing Zhu (Inorganics)
Currently, the electrochemical reduction of carbon dioxide faces significant challenges, including poor selectivity for C2 products and low conversion efficiency. An effective strategy for optimizing the reduction reaction pathway and enhancing catalytic performance involves manipulating highly unsaturated atomic sites on the catalyst’s surface, thereby increasing the number of active sites. In this study, we employed sodium dodecylbenzenesulfonate (SDBS) as a surfactant in the electrodeposition method to synthesize copper cubes encapsulated with an amorphous shell (100 nm–250 nm) containing numerous defect sites on its surface. The electrocatalytic CO2 reduction reactions in an H-type reactor showed that, compared to ED-Cu synthesized without additives, AS (amorphous shell)-Cu-5 exhibited a Faradaic efficiency value for ethylene that was 1.7 times greater than that of ED-Cu while significantly decreasing the Faradaic efficiency of hydrogen production. In situ attenuated total reflectance surface-enhanced infrared spectroscopy (ATR-SEIRAS) revealed that introducing an amorphous shell and abundant defects altered both the intermediate species and reaction pathways on the AS-Cu-5 catalyst’s surface, favoring C2H4 formation. The density functional theory (DFT) calculations further confirmed that amorphous copper lowers the energy barrier required for C-C coupling, resulting in a marked enhancement in FE-C2H4. Therefore, additive-assisted electrodeposition presents a simple and rapid synthesis method for improving ethylene selectivity in copper catalysts.